INTEGRATED TRANSPORT SYSTEM TOWARD SUSTAINABLE TRAVEL BEHAVIOR FOR WORK COMMUTING TRAVEL FROM BEKASI TO JAKARTA - Safitri, Rinawanti; Sebhatu, Samuel Petros; Priyanto, Sigit (Jurnal Transportasi, 2015)
Abstract Due to the inadequacy of public transport and high critical level of congestion in Jakarta Metropolitan Area, implementing sustainable transport for urban future transport improvement is necessary. Critical transport situation in Jakarta Metropolitan Area has pointed the importance of implementation integrated transport system to increase people accessibility. This study is conducted to identify strategic issues in integrated transport system at operational and policy levels toward sustainable mobility, transport equity, and door to door service. According to research aim, explanatory case study is used to build an understanding the current situation. The results indicate that integrated transport system is not fully implemented yet and it found a lot of missing links and barriers in integrated transport system attributes. Moreover, transportation planning at national to local levels is not synchronous which have impacted to the implementation of integrated transport. Keywords: integrated transport, transport system, transport policy, mobility  Abstrak Tidak memadainya transportasi umum dan tingginya tingkat kemacetan lalulintas di Kota Metropilitan Jakarta menyebabkan diperlukannya penerapan transportasi yang berkelanjutan untuk perbaikan transportasi perkotaan di masa depan. Situasi transportasi di Jakarta yang telah kritis ini menunjukkan pentingnya penerapan sistem transportasi terpadu untuk meningkatkan aksesibilitas masyarakat. Penelitian ini dilakukan untuk mengidentifikasi isu-isu strategis dalam sistem transportasi terpadu di tingkat-tingkat operasional dan kebijakan terhadap mobilitas yang berkelanjutan, ekuitas transportasi, dan layanan pintu ke pintu. Penelitian ini menggunakan studi kasus untuk menjelaskan situasi yang terjadi saat ini. Hasil penelitian menunjukkan bahwa sistem transportasi terpadu belum sepenuhnya dilaksanakan dan ditemukan banyak missing links dan hambatan dalam atribut-atribut sistem transportasi yang terintegrasi. Selain itu, perencanaan transportasi di tingkat nasional dan di tingkat daerah tidak sejalan yang berdampak pada pelaksanaan transportasi terpadu. Kata-kata kunci: transportasi terpadu, sistem transportasi, kebijakan transportasi, mobilitas